Antibacterial Activity Test of Endophytic Microbes of Bird's Nest Fern (Asplenium nidus) Against Propionibacterium acnes Bacteria - Roza, Rodesia Mustika; Wardani, Cloudia Pramesti Kusuma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Acne is a widespread skin treatment frequently seen within Indonesia. This condition, also known as Acne vulgaris, arises from an infection or irritation affecting the pilosebaceous units. This is caused by obstructions and build-up of keratin, which are spurred on by the existence of Propionibacterium acnes bacteria. Current acne treatment uses a lot of synthetic antibiotics, as a result if used for a long period of time it can increase resistance so that acne is difficult to cure. One effort to overcome drug resistance is to utilize endophytic bacteria that have the ability to produce similar compounds from their host plants including antibacterial compounds. Plants that have the potential as antibacterials are bird's nest ferns (Asplenium nidus). The content of this plant is flavonoids, alkaloids, terpenoids, phenolics, tannins, and saponins. This research intends to evaluate the antibacterial properties of endophytic microorganisms derived from the A. nidus plant against P. acnes bacteria. The assessment of antibacterial capabilities was performed through the utilization of the agar disk diffusion technique. The separation process resulted in a total of 16 endophytes, which were further categorized into 11 bacterial strains and 5 fungal strains. Evaluation of the antibacterial properties of the endophytes revealed that 9 bacterial endophyte strains could impede the proliferation of P. acnes, with strain BRAN 10 exhibiting the greatest antibacterial effect, characterized by a zone of inhibition measuring 13.47 mm in diameter. Isolate JDAN 3 demonstrated the most potent antifungal activity among the endophytes, marked by an inhibition zone diameter of 9.9 mm.